A rare childhood uterine malignancy combined with complete uterine inversion - Klenovská, Lucie; Meixnerová, Ivana; Minář, Luboš; Ježová, Marta (Ceska gynekologie, 2025)
OBJECTIVE: An overview of the types of uterine sarcoma, supplemented by an illustrative case report of a rare uterine childhood tumor. CASE REPORT: Our case report describes the case of a 9-year-old girl with a 15-cm tumor in the abdominal cavity, which prolapsed vaginally before introitus during a clinical examination of the abdominal wall causing life-threatening bleeding. This bleeding was stopped by ligation of the tumor pedicle and its resection. Histological examination of the resected specimen described Müllerian adenosarcoma of the uterus. Based on the staging, laparoscopic hysterectomy with bilateral salpingectomy was indicated by the oncogynecological committee. The operation was performed without complications, and intraoperatively, a complete inversion of the uterus was diagnosed.
Keywords: Müllerian adenosarcoma; adenosarkom; Child; Uterine Neoplasms; inverze dělohy; ženské pohlaví; lidé; dítě; hysterektomie; Adenosarcoma; leiomyosarcoma; Hysterectomy; Uterine Inversion; uterine inversion; endometrial stromal sarcoma; Humans; Leiomyosarcoma; uterine sarcoma; Female; nádory dělohy